Transcriptomic profiles reveal differences between the right and left ventricle in normoxia and hypoxia - Gorr, Matthew W. (Physiol Rep, 2020)
Chronic hypoxia from diseases in the lung, such as pulmonary hypertension, pulmonary fibrosis, and chronic obstructive pulmonary disease, can increase pulmonary vascular resistance, resulting in hypertrophy and dysfunction of the right ventricle (RV). In order to obtain insight into RV biology and perhaps uncover potentially novel therapeutic approaches for RV dysfunction, we performed RNA‐sequencing (RNA‐seq) of RV and LV tissue from rats in normal ambient conditions or subjected to hypoxia (10% O(2)) for 2 weeks. Gene ontology and pathway analysis of the RV and LV revealed multiple transcriptomic differences, in particular increased expression in the RV of genes related to immune function in both normoxia and hypoxia. Immune cell profiling by flow cytometry of cardiac digests revealed that in both conditions, the RV had a larger percentage than the LV of double‐positive CD45(+)/CD11b/c(+) cells (which are predominantly macrophages and dendritic cells). Analysis of gene expression changes under hypoxic conditions identified multiple pathways that may contribute to hypoxia‐induced changes in the RV, including increased expression of genes related to cell mitosis/proliferation and decreased expression of genes related to metabolic processes. Together, the findings indicate that the RV differs from the LV with respect to content of immune cells and expression of certain genes, thus suggesting the two ventricles differ in aspects of pathophysiology and in potential therapeutic targets for RV dysfunction.